Impact of learning conditions on young FL learners' motivation - Mihaljević-Djigunović, Jelena (Array, 2009)
The author compares attitudes and motivation of two cohorts of young EFL learners in the Croatian educational context. One cohort was learning under very favourable, experimental conditions (small group size, intensive learning, teachers trained for work with young learners), the other under non-experimental conditions. Differences in attitudes and motivation are explained in terms of differences in learning conditions.